Pengaruh Asosiasi Merek dan Citra Merek terhadap Loyalitas Merek Melalui Kepercayaan Merek pada Azarine Cosmetics: Studi pada Followers Instagram Azarine Cosmetics - Aritonang, Chaterine; Nurhadi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
In the face of increasingly tight business competition, a company needs to have a strong brand as a unique and attractive identity for consumers. A strong brand can create brand loyalty. However, this can also be driven by brand trust that is built with strong brand associations and brand image from customers. This study aims to analyze the influence of brand associations and brand image on brand loyalty with brand trust as an intervening variable on Azarine Cosmetics (study on Azarine Cosmetics Instagram followers). This study uses a quantitative approach. With a population of Azarine Instagram followers and a sample of 160 respondents. The sampling technique used in this study is purposive sampling. The analysis technique used is partial least squares (PLS) analysis using SmartPLS software. The results of this study show that brand associations and brand image significantly influence brand trust. Brand association does not significantly influence brand loyalty. Brand image and brand trust significantly influence brand loyalty. Brand associations and brand image through brand trust significantly influence brand loyalty.